Face numbers of pseudomanifolds with isolated singularities - Novik, Isabella; Swartz, Ed (MATHEMATICA SCANDINAVICA, 2012)
We investigate the face numbers of simplicial complexes with Buchsbaum vertex links, especially pseudomanifolds with isolated singularities. This includes deriving Dehn-Sommerville relations for pseudomanifolds with isolated singularities and establishing lower and upper bound theorems when the singularities are also homologically isolated. We give formulas for the Hilbert function of a generic Artinian reduction of the face ring when the singularities are homologically isolated and for any pure two-dimensional complex. Some examples of spaces where the $f$-vector can be completely characterized are described. We also show that the Hilbert function of a generic Artinian reduction of the face ring of a simplicial complex $Δ$ with isolated singularities minus the $h$-vector of $Δ$ is a PL-topological invariant.